A Study of Women in Educational Leadership in Dubai: A Private Sector Perspective - Sim, Rachael Elizabeth (2006)
Leadership continues to be perceived as a male dominated realm. When women enter the world of educational leadership, their narratives show that their experience of leadership is unique. The purpose of this study is to examine the experiences of women in leadership in British curriculum private schools in the Emirate of Dubai. There were four main areas of discussion. Firstly, the impact of culture on the experience of female leadership was explored. Secondly, the leadership styles of the women were examined. In addition to this, the impact of gender was discussed with specific reference to stereotypes and prejudice. Finally, the reasons why the women believed they had been successful were explored. Six women were interviewed their responses were analysed in relation to current thinking on educational leadership. The findings of this study show that the predominant culture in the UAE continues to impact on the way women lead and the leadership styles women tend towards. Gender is not central to the way women perceive themselves, but women are stereotyped to some extent. These stereotypes are not always necessarily negative and tend to place women in nurturing roles. The gender balance of senior management teams is biased and this could be due to the patriarchal nature of the culture in Dubai. Women were successful because they were able to adapt to the expectations of others, without compromising their own beliefs of what constitutes effective leadership.